GENDER DIVERSITY DAN GOOD CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS - Guruh Dwi Samudra (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This study aims to examine and analyze the effect of gender diversity and good corporate governance on financial distress. The criteria for financial distress in this study are measured by negative net income for two consecutive years. Good corporate governance in this study uses elements including the board of commissioners, independent commissioners, and institutional ownership. This research refers to research by Ayuningtyas (2013) and Kristanti, et al. (2016). The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2014-2016. The sample in this study obtained 380 companies selected based on purposive sampling method. The data analysis used in this study is logistic regression analysis with SPSS ver 20 software. The results of this study prove that the board of commissioners and gender diversity have a negative effect on financial distress. While the independent board of commissioners has no effect on financial distress and institutional ownership has a positive effect on financial distress.